A mutation of the H-loop selectively affects rhodamine transport by the yeast multidrug ABC transporter Pdr5 - Ernst, Robert (National Academy of Sciences, 2008)
The yeast ABC transporter Pdr5 plays a major role in drug resistance against a large number of structurally unrelated compounds. Although Pdr5 has been extensively studied, many important aspects regarding its molecular mechanisms remain unresolved. For example, a striking degeneration of conserved amino acid residues exists in the nucleotide binding domains (NBDs), but their functional relevance is unknown. Here, we performed in vivo and in vitro experiments to address the functional asymmetry of NBDs. It became evident by ATPase activity and drug transport studies that catalysis at only one of the two NBD composite sites is crucial for protein function. Furthermore, mutations of the proposed “catalytic carboxylate” (E1036) and the “catalytic dyad histidine” (H1068) were characterized. Although a mutation of the glutamate abolished ATPase activity and substrate transport, mutation of H1068 had no influence on ATP consumption. However, the H1068A mutation abolished rhodamine transport in vivo and in vitro, while leaving the transport of other substrates unaffected. By contrast to mammalian P-glycoprotein (P-gp), the ATPase activity of yeast Pdr5 is not stimulated by the addition of substrates, indicating that Pdr5 is an uncoupled ABC transporter that constantly hydrolyses ATP to ensure active substrate transport. Taken together, our data provide important insights into the molecular mechanism of Pdr5 and suggest that not solely the transmembrane domains dictate substrate selection.